SAT0281 Impact of enthesitis in 1505 brazilian patients with spondyloarthritis. (23rd January 2014) - Carneiro, S.; Bortoluzzo, A.; Gonçalves, C.; Silva, J.A.; Ximenes, A.C.; Bértolo, M.; Ribeiro, S.; Keiserman, M.; Menin, R.; Azevedo, V.; Vieira, W.; Albuquerque, E.; et al.
Abstract : Background: The spondyloarthritides (SpA) represent a group of chronic diseases that affect around 1% of the population. Enthesitis is a frequent clinical complaint in SpA patients that need to be better investigated Objectives: To analyze the impact of the entheseal inflammatory involvement in a large Brazilian cohort of SpA patients. Methods: A common protocol of investigation was prospectively applied to 1505 SpA patients in 29 centers distributed through the main geographical regions in Brazil. Clinical and demographic variables and disease indexes (BASDAI, BASFI, BASRI, ASQoL) were investigated. MASES (Maastricht Ankylosing Spondylitis Enthesitis Score) was used to investigate the entheseal component. Ankylosing spondylitis (AS) was the most frequent disease (65.4%) that also included psoriatic arthritis (18.4%), undifferentiated SpA (6.7%), reactive arthritis (3.3%), and enteropathic arthritis (3.2%). Results: Enthesitis was referred by 54% of the SpA patients, with a mean of 2.12±2.98 enthesis affected. It was present in 53.3% of the AS patients, 54.4% in psoriatic arthritis, and 70.4% in undifferentiated SpA. Enthesitis was significantly more frequent in patients with axial + peripheral joint involvement compared to isolated involvement (p<0, 001). The frequency of enthesitis was higher in females (p=0.014), in those who presented partial or total work incapacity (p<0.001), and in those who practice lower daily hours of exercise (p=0.002). There was also statistical correlation with higher erythrocyte sedimentation rate (27.25±23.63 vs. 22.20±20.55; p<0.001), higher C-reactive protein (11.72±24.77 vs. 8.12±16.02; p=0.004) and higher visual analogue scales of disease activity by the patient (5.53±2.69 vs. 4.07±2.88; p<0, 001) and the physician (4.64±2.56 vs. 2.95±2.45; p<0, 001). Patients with enthesitis presented higher BASFI (5.17±2.64 vs. 3.82±2.76; p<0, 001), BASDAI (4.95±2.22 vs. 3.32±2.26; p<0, 001) and ASQoL (9.08±5.29 vs. 6.19±5.08; p<0, 001) indexes. Conclusions: The presence of enthesitis in SpA patients was frequent and caused a significant negative impact in the quality of life, associated to a more extensive joint involvement and functional incapacity. References: Doward LC et al. Development of the ASQoL: a quality of life instrument specific to ankylosing spondylitis. Ann Rheum Dis 2003;62:20-6 Jones SD et al A new scoring system for the Bath Ankylosing Spondylitis Metrology Index (BASMI). J Rheumatol 1995;22:1609 Malorie P et al. A new approach to defining functional ability in ankylosing spondylitis: the development of the Bath Ankylosing Functional Index. J Rheumatol 1994;21: 2281-5 Sampaio-Barros PD et al. Primary ankylosing spondylitis: patterns of disease in a Brazilian population of 147 patients. J Rheumatol 2001;28:560-5. Disclosure of Interest: None Declared